2017
DOI: 10.1111/jpm.12400
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the value of mental health nurses working in primary care in England: A qualitative study

Abstract: Aims/Question General practice is typically the first point of access to healthcare. This study explores what value a Primary Care Liaison Nurse (PCLN) service, established in 2011, can bring to people with mental health problems in primary care. Method Semi-structured interviews were used to elicit participants' experiences and perspectives on the value of a PCLN service. Participants included ten interviews with seven general practitioners and three senior practitioners working in primary care mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…On one side, the community mental health nurses, the psychiatrist and partly also the patients expressed the point of view that the referral to primary healthcare is an accomplishment and a sign of recovery. On the other side, the GP's saw the referral as little more than a practical change, which is an observation that has been made before (McLeod & Simpson, ). When asked for tangible differences after the referral to primary healthcare, the GP's only identified practical differences (like nearer to home or getting less time from the healthcare professional).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On one side, the community mental health nurses, the psychiatrist and partly also the patients expressed the point of view that the referral to primary healthcare is an accomplishment and a sign of recovery. On the other side, the GP's saw the referral as little more than a practical change, which is an observation that has been made before (McLeod & Simpson, ). When asked for tangible differences after the referral to primary healthcare, the GP's only identified practical differences (like nearer to home or getting less time from the healthcare professional).…”
Section: Discussionmentioning
confidence: 74%
“…Other examples include a recently published review describing the association between continuity of care and health outcomes (Weaver, Coffey, & Hewitt, ) and a qualitative study about mental health care planning among mental health nurses working in primary care in England, that concludes that clear referral criteria are needed (McLeod & Simpson, ). Studies like these add to the knowledge base on treating patients with SMI in primary healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…15 Several studies have evaluated the use of mental health nurses in primary care. 16,17 Redeploying trained community psychiatry nurses into general practice across primary care networks has the potential to result in positive mental health patient outcomes, 16 improved access to mental health care, shorter waiting times, and better integrated care. 17 In addition, studies have reported reduced stigma for accessing mental health services within primary care.…”
Section: ) Mental Health Professionals In General Practicementioning
confidence: 99%
“…17 In addition, studies have reported reduced stigma for accessing mental health services within primary care. 17…”
Section: ) Mental Health Professionals In General Practicementioning
confidence: 99%
“…Based on the IMPACT study, Saur et al. () described how the psychiatric nurses took on a “unique role of mental health nurses in primary care.” A recent study of mental health nurse‐led primary care liaison in the United Kingdom showed that mental health nurses can improve the quality of care and can be successfully integrated into primary care (McLeod & Simpson, ).…”
Section: Introductionmentioning
confidence: 99%